(3GdCMcGe GdTQYjI GdcHQi ef MOjK QShd Gddg Udi Gddg Ydjg hSdes - (3YHO GdMb Hf YHO GdQMef Hf YHO Gddg GdCROj GdETHjdj, CHh eMeO, GdeYQha H` GHf GdNQGW,J (B581 (3g` s
(3ChdgG (B:s
(3jHJOF HcJGH GdEjeGf s
(3BNQgG (B:s
(3hjfJgi HHGH ehbJ UdGI GdaLQ s
(3GdfSNI HgG MhGTs
(3Ydjg Jedc eDQN HSfI (B852(3g`s
(3hJhbjY dGHf MLQ GdYSbdGfi Ydi GdETgGO Hhba GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs